2017
DOI: 10.1016/j.chom.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent H3N2 Viruses Have Evolved Specificity for Extended, Branched Human-type Receptors, Conferring Potential for Increased Avidity

Abstract: SUMMARY Human and avian influenza viruses recognize different sialic acid-containing receptors, referred to as human-type (NeuAcα2-6Gal) and avian-type (NeuAcα2-3Gal) respectively. This presents a species barrier for aerosol droplet transmission of avian viruses in humans and ferrets. Recent reports have suggested that current human H3N2 viruses no longer have strict specificity towards human-type receptors. Using an influenza receptor glycan microarray with extended airway glycans we find that H3N2 viruses ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
245
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(281 citation statements)
references
References 48 publications
15
245
0
1
Order By: Relevance
“…We9, 16 and others19 have reported that some human influenza viruses preferentially recognize longer α2,6‐linked N‐glycan sialosides. However, the detailed interactions between the HAs and the large sialoside receptors have not yet been closely investigated.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…We9, 16 and others19 have reported that some human influenza viruses preferentially recognize longer α2,6‐linked N‐glycan sialosides. However, the detailed interactions between the HAs and the large sialoside receptors have not yet been closely investigated.…”
mentioning
confidence: 89%
“…Based on previous avidity assays for HK/68,9 the N‐glycan with one LacNAc (similar to 4 ) displays weak binding, while a glycan with two LacNAc repeats like N‐glycan 5 binds with higher avidity. From the NMR perspective, STD data obtained of N‐glycan 5 under diamagnetic conditions also showed glycan binding to the hemagglutinin, involving the Neu5Ac residues, but no discrimination of the specific involvement of A and/or B branches could be evidenced (Figure 3 left) owing to the chemical‐shift degeneracy.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…This study has proposed a bidentate binding model, where these human-type receptors with elongated branches bind to two subunits of the same HA, increasing the avidity of recent H3 viruses for the complex forms of human SAα2,6 receptors. 50 The effect of receptor-binding variations in human H3 viruses through all these years has represented a scientific challenge for virus isolation, antigenic characterization, and vaccine strain selection. A transition in in vitro systems has required moving from only chicken to a broad source as turkey, guinea pig, or human RBCs, without any success.…”
mentioning
confidence: 99%
“…Multiple types of molecules could be used as viral receptors (Baranowski et al, 2001;Casasnovas, 2013), including protein (Li, 2016;Wang, 2002;Yan et al, 2012), carbohydrate (Isa et al, 2006;Peng et al, 2017) and lipid (Mazzon and Mercer, 2014). How to select receptors by the virus is an important unsolved question (Casasnovas, 2013;Grove and Marsh, 2011;Li, 2016;Marija Backovic, 2012).…”
Section: Introductionmentioning
confidence: 99%